Transfer Kebijakan pada Rencana Induk Kota Cerdas Kabupaten Karo dalam Aspek Smart Governance - Ambarita, Andar Maruli; Trimurni, Februati (Universitas Pahlawan Tuanku Tambusai, 2024)
Smart city is a concept that refers to a system of ideas about city or district development that involves the application of technology and inovation programs into the dimensions of government, economy, society, city branding, life, and the environment. However, it becomes a question of where this concept comes from and why the local government of Karo Regency adopts this foreign concept to government performance. This research uses a descriptive qualitative research method with an inductive analysis approach. The results of this study found that the concepts in the development of Smart City in the Smart City dimension of Karo Regency are policies transferred from outside and fully adopted by the Karo Regency local government along with the entire framework and model but the implementation programs are still sourced from the local apparatus itself. As conclusion, The main finding is that the description of how Smart City in a local government in the future is largely determined by how interested public officials define Smart City.